Bipolar Disorder in Children With ADHD: A Clinical Sample Study. (July 2017) - Donfrancesco, Renato; Di Trani, Michela; Andriola, Elda; Leone, Daniela; Torrioli, Maria G.; Passarelli, Francesca; DelBello, Melissa P.
Objective: To explore the impact of early-onset bipolar disorder (pediatric bipolar disorder [PBD]) on ADHD.Method: We compared ADHD symptom severity, ADHD subtype distribution, and rates of comorbid and familial psychiatric disorders between 49 ADHD children with comorbid PBD and 320 ADHD children without PBD.Results: Children with ADHD and PBD showed higher scores in the Hyperactive and Inattentive subscales of the ADHD Rating Scale, than children with ADHD alone. The frequency of combined subtype was significantly higher in ADHD children with PBD, than in those with ADHD alone. ADHD children with PBD showed a higher rate of familial psychiatric disorders than ADHD children without PBD. The rate of conduct disorder was significantly greater in children with PBD and ADHD compared with children with ADHD alone.Conclusion: ADHD along with PBD presents with several characteristics that distinguish it from ADHD alone, suggesting that these may be distinct disorders.